Characterization of Rust Layers Formed on Nickel-Alloyed Steel Under Different Exposure Sites - T. RESABAL, VANNIE JOY; OHTSUKA, TOSHIAII (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The rust layers formed on Fe-Ni steel with varying nickel content exposed to open atmosphere in three different sites of Japan for three (3) years were characterized using electrochemical impedance (EIS) and near infrared reflectance-absorbance spectroscopy (NIR-RAS) under wet condition at RH 90%. To determine the saturation amount of water in the rust layer, the amount of water vapor absorbed was measured using Mettler balance and the apparent diffusion coefficients were calculated using the semiinfinite model of diffusion. Results showed that the apparent diffusion coefficient increased with increasing amount of airborne salts. This increase in diffusion coefficient is an indication that the rust layer formed under high chloride environment has lessened its protective ability as evidenced by the increase in water diffusing into the rust layer. Increasing the amount of nickel in steels has proved to decrease the diffusion coefficient, thereby, making the rust layer more protective. To supplement the results of NIR-RAS, the impedance diagram of the rusted surface of the steels was analyzed. Results showed that the rust layer formed in the site with relatively high amount of airborne salt revealed high conductivity under wet condition, which is an inclication that the rust layer has absorbed a relatively high amount of water. Moreover, it was also found that with increasing nickel content, the conductivity is decreased.